COMMANDE SANS CAPTEUR DE LA MACHINE SYNCHRONE A RELUCTANE VARIABLE - نصر, غانية; حسين, قرفي; عبد الله, بن عمر (University Of El Oued, 2020)
The objective of this these is to develop an observer for the speed control of the synchronous reluctance machine without mechanical speed sensor based on the MRAS technique. This technique consists of controlling this motor without the speed sensor, which gives us robust control and great flexibility of use. الهدف من هده المذكرة هو تطوير مقدر السرعة للتحكم بدون مستشعر السرعة الميكانيكي لآلة المتزامنة ذات ممانعة متغيرة على أساس تقنية MRAS. تتمثل هذه التقنية في التحكم في هذا المحرك دون استخدام المستشعر مما يمنح المحرك مرونة كبيرة في الاستخدام.
Machine éléctrique مذكرة ماستر تخصص
Keywords: Key Words : Sensorless control, Synchronous Reluctance Motor, vector control; كلمات مفتاحية :تحكم بدون حساس ، ماكنة متزامنة ذات ممانعة متغيرة ، تحكم شعاعى